Why India still fighting for first FDI receipt country?. (30th January 2020) - Kumari, Reenu; Sharma, Anil Kumar
In recent times China and India have undergone outstanding economic progress but still China growing more than India, so everyone has curiosity to know the reason why India is still behind the China. Thus, this paper has two main objectives: first, to explore the major reasons for the variation between China's and India's FDI inflows. The five main reasons which affect the variation of China and India's FDI inflows are: round tripping, disparity in policy and non-policy determinants of FDI; value of definition of FDI is different, changes in policies and schemes and freedom and obstacles also matter; second, to examine the determinants of FDI which affect China's and India's FDI inflows for the period of 1990–2014; using the OLS method with unit roots test to find out determinants of FDI inflows in both countries. Moreover, at last in this paper we show that comparison between impact of determinants of FDI in China and India.